MORPHOLOGY OF THE DIGESTIVE TRACT OF THE FARMED NILE TILAPIA FISH Orechromis niloticus (Linnaeus, 1758) FROM EASTERN NIGERIA - Ikpegbu , E.; Ahaotu, I. J.; Ibe, C. S.; Oke, A. O.; Agbakuru, I. K.; Nnadozie, O.; Nlebedum , U. C. (Nigerian Journal of Fisheries, 2018)
The digestive tract morphology of the Nile Tilapia (Orechromis niloticus) was investigated to help understand its digestive biology, provide data for further studies including clinical cases. The lips, tongue, and oesophagus were lined by stratified squamous epithelium containing, mucous cells and lymphocytes. This protective type epithelial covering can be associated with the majorly herbivorous feeding habit. The oesophageal stratified squamous epithelium contained abundant Periodic Acid Schiff (PAS) positive mucous cells. The U-shaped stomach was bound cranially by oesophageal sphincter and pyloric sphincter caudally. The stomach mucosal simple columnar epithelial lining contained PAS positive apical mucin. The laminar propris containing gastric glands were only seen in the cardiac and fundic regions, the pyloric laminar propria contained well developed PAS positive mucous glands with myoepithlial cells in the enveloping connective tissue. These mucous glands with further staining showed a predominance of acid mucin. The intestinal mucosa was lined by simple columnar cells containing abundant PAS positive goblet cells and lymphocytes. The distal intestine contained aggregated lymphoid cells in localised areas of laminar propria. From this study, the digestive tract of the farmed Nile Tilapia from Eastern Nigeria has shown morphological features adaptive for its herbivorous feeding habit in a cultured environment.